(untitled) (Current Horticulture, 2024)
The experiment was conducted to evaluate the effect of salinity on horticultural traits of grafted tomato (Solanum lycopersiocon Mill.) onto brinjal (Solanum melongena L.) rootstock and to find out the best salt tolerance or resistant rootstock/graft combination during 2021-22 at ICAR-IIVR KVK, Bhadohi, Uttar Pradesh. Three rootstocks (IC-111056, IC-354557, and Surya) and graft between three different scions (Kashi Aman, Kashi Chayan and NS-4266) were compared with their scions. Among rootstock, IC-111056 and IC-354557 were observed highly salt tolerant to saline condition which could be used as rootstock for further crop production in saline conditions and its use in conventional breeding programme to develop salt tolerant/resistant variety.